Modelling of the relationship of adiabatic shear and cutting conditions for higher cutting speed ranges - Li, Guohe (Strojniški vestnik, 2017)
The serrated chip is a typical characteristic of high-speed cutting due to the occurrence of adiabatic shear. Based on an adiabatic shear sensitivity index proposed via linear perturbation analysis, which considers the pressure-shear condition in machining, the relationship of adiabatic shear and cutting conditions is established. The corresponding relation between the cutting conditions and the deformation conditions is established based on the model of a parallel boundary shear zone. The influence of cutting parameter on adiabatic shear is analysed, and the results show that the adiabatic shear in high speed machining tends to occur under the condition of higher cutting speed, greater depth of cut and smaller rake angle. An orthogonal cutting experiment was performed to validate the proposed model. Furthermore, the influence mechanism of cutting conditions on adiabatic shear is discussed in detail, and one application of the model is introduced.
Keywords: adiabatni strig; indeks občutljivosti; linearna perturbacijska analiza; nazobčani odrezki; rezalni parametri; visokohitrostno odrezavanje